Adaptive processing of geochemical analysis by means of spline model - Білецький, А. Я.; Шелевицький, І. В.; Шутко, В. М.; Юрко, Ю. В. (Proceedings of National Aviation University (archive), 2000)
Proposed is adaptive algorithm of geochemical analysis processing by means of spline model. Demonstrated is the possibility of splines to reveal heterogeneous fields in the composition of iron ore which, because of considerable dispersion of random component, is practically impossible to reveal